Calculus

posted by .

Use newtons method and the function f(x)=x^2-a to derive the mechanics rule.
Mechanics Rule for approaching sqrt(a), a>0, is
Xn+1=1/2(Xn+a/Xn), n=1,2,3,...

  • Calculus -

    Newton's method for the root of f(x) is:

    x_{n+1} = x_{n} - f(x_{n})/f'(x_{n})

    = x_{n} - (x_{n}^2 - a)/(2 x_{n}) =

    1/2 (x_{n} + a/(x_{n}))

    This rule is not so convenient, because you need to divide by x_{n} at each step (division is slower than multiplication). A rule without division can be obtained by writing the square root as the root of the function:

    f(x) = x^(-2) - 1/a

    Newton's method then yields:

    x_{n+1} = x_{n} -
    ( x_{n}^(-2) - 1/a)/(-2x_{n}^(-3)) =

    1/2 x_{n} (3 - x_{n}^2/a)

    So, in each step you now only have a division by a, so you only have to compute 1/a once.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. limit calc question

    2 questions!!! 1. Limit X approaching A (X^1/3-a^1/3)/ x-a 2. LiMIT x approaching 0 (1/3+x – 1/3) /x On the first, would it help to write the denominator (x-a) as the difference of two cubes ((x^1/3 cubed - a^1/3 cubed) second. use …
  2. pre-cal

    Find the roots of the function f(x)= x^2+2x+2 Determine f(x) a) (x+1-i)(x+1+i) b)(x+1-i sqrt of 2)(x+1+i sqrt of 2) c)x-1+i)(x-1-i) d)x-1+i sqrt of 2) (x-1-i sqrt of 2) Please Help! For all of these, use the rule [f(x) + ai]*[(f(x) …
  3. Calculus

    Can anyone explain how to use the chain rule and power rule together to find the first derivative and please do these examples. f(x) = -3x^4/(sqrt(4x-8)) g(x) = ((2x+5)/(6-x^2)^4 g(x) = (8x^3)(4x^2+2x-3)^5 y = [1/(4x+x^2)^3]^3 Thank …
  4. calculus

    Find the derivative of the function below in two ways. F(x) = (x - 7 x sqrt(x)) / sqrt(x) (a) By using the Quotient Rule. (b) By simplifying first.
  5. Calculus

    Use the General Power Rule or the Shifting and Scaling Rule to find the derivative of the function given below. y = e^(16 – 3x^2)
  6. Calculus

    Am I right so far? G(x)=e^x sqrt(1+x^2) =e^x(1+x^2)^1/2 =e^x(1/2)(1+x^2)^-1/2(2x) + e^x(1+x^2)^1/2 So I used product rule, chain rule, and exponential function with base e
  7. Calculus

    Match the rule with the title: ____ 3. d/dx [f(x)/g(x) ]=(g(x) f^' (x)-f(x) g^' (x))/[g(x)]^2 ____ 4. d/dx [f(g(x))]=f^' (g(x))∙g'(x) ____ 5. d/dx [f(x)∙g(x)]= f(x) g^' (x)+g(x) f^' (x) ____ 6.d/dx [x]=1 ____ 7. d/dx [f(x)+g(x)]= …
  8. Calculus

    So, I have a homework question on The Quotient Rule (taking derivitives) and I would like to know if I did it right. Calculate: y=(1/sqrt(x))-(1/(5th root of x^3). My 1st step was to change the sqrt to x^1/2, and the 5th root to x^1/5+^3. …
  9. Math (Calculus)

    Hello, Could somebody please help me with the following question?
  10. Calculus

    We just learned derivatives and now on the Chain Rule. y = r/[(sqrt)(r(sqrd)+1)] y' = [[(sqrt)(r(sqrd)+1)(r)'] - [(r)(sqrt)(r(sqrd)+1)']] / [(sqrt)(r(sqrd)+1)](sqrd) y' = (sqrt)(r(sqrd)+1) - r[1/2(r(sqrd)+1)(raised to -1/2)](2r) My …

More Similar Questions